The Upcoming Epidemic of Heart Failure in South Asia. (October 2020) - Martinez-Amezcua, Pablo; Haque, Waqas; Khera, Rohan; Kanaya, Alka M.; Sattar, Naveed; Lam, Carolyn S.P.; Harikrishnan, Sivadasanpillai; Shah, Sanjiv J.; Kandula, Namratha R.; Jose, Powell O.; Narayan, K. M. Venkat; Agyemang, Charles; et al.
Abstract : Currently, South Asia accounts for a quarter of the world population, yet it already claims ≈60% of the global burden of heart disease. Besides the epidemics of type 2 diabetes mellitus and coronary heart disease already faced by South Asian countries, recent studies suggest that South Asians may also be at an increased risk of heart failure (HF), and that it presents at earlier ages than in most other racial/ethnic groups. Although a frequently underrecognized threat, an eventual HF epidemic in the densely populated South Asian nations could have dramatic health, social and economic consequences, and urgent interventions are needed to flatten the curve of HF in South Asia. In this review, we discuss recent studies portraying these trends, and describe the mechanisms that may explain an increased risk of premature HF in South Asians compared with other groups, with a special focus on highly relevant features in South Asian populations including premature coronary heart disease, early type 2 diabetes mellitus, ubiquitous abdominal obesity, exposure to the world's highest levels of air pollution, highly prevalent pretransition forms of HF such as rheumatic heart disease, and underdevelopment of healthcare systems. Other rising lifestyle-related risk factors such as use of tobacco products, hypertension, and general obesity are also discussed. We evaluate the prognosis of HF in South Asian countries and the implications of an anticipated HF epidemic. Finally, we discuss proposed interventions aimed at curbing these adverse trends, management approaches that can improve the prognosis of prevalent HF in South Asian countries, and research gaps in this important field.